(untitled) (Baghdad Science Journal, 2005)
The use of male mothers fur c meat Fabro to learn Effect concentrations of ammonium chloride NH4CL and Bacarbonnat sodium NaHCO3 in drinking water by heat stress and Altsoam during heat stress on some of the qualities of productivity and Alvesrgih divided animals to 6 transactions, namely: - control without adding NH4CL, NaHCO3 and Altsoam (treatment 1) Altsoam-1200 of 7-4 weeks old chicken meat to heat patrol 25-34-25 .. 7 weeks old Weight was measured gravimetric vivo increase feed consumption